Systematic approach to evaluating environmental and ecological technologies for wastewater treatment. (March 2019) - Su, Xiaoling; Chiang, Penchi; Pan, Shuyuan; Chen, Guangjiao; Tao, Yinren; Wu, Gaojie; Wang, Feifei; Cao, Wenzhi
Abstract: Evaluating the performance of wastewater treatment represents a challenging and complex task as it usually involves engineering, environmental and economic (3E) factors. In this study, we developed an 3E triangle model to evaluate the performance of environmental technologies (i.e., anaerobic-anoxic-oxic reactors, oxidation ditches, and membrane bioreactors) and ecological technologies (i.e., stabilization ponds, constructed wetlands, and slow-rate systems) for wastewater treatment. A total of 17 key performance indicators, such as energy consumption, pollutant removal, global warming potential and wastewater treatment fees, were considered in the 3E triangle model. The results indicated that, in terms of engineering performance, both the membrane bioreactors and constructed wetlands were stable, effective and reliable during their operating periods. When the environmental impacts of wastewater treatment technologies were compared via a life cycle assessment, the ecological technologies showed superior performance, in terms of environmental impacts, especially for the global warming potential and eutrophication potential. In general, environmental technologies exhibited higher treatment fees and unit construction costs because of their large power consumption and equipment costs. In contrast, ecological technologies had higher unit land use due to their large area requirements and low treatment capacity. In overall, both the membrane bioreactors and constructed wetlands showed excellent overall performance in the 3E triangle model. Wastewater treatment plant are typical case studies for addressing the interactions of water and energy elements. Reducing energy consumption is a hotspot for the research field of membrane bioreactors, while constructed wetlands are continually improved and optimized to have broad applications for rural wastewater treatment. Highlights: MBRs and constructed wetlands are superior in terms of engineering performance. Ecological technologies have superior performance in terms of environmental aspect. Environmental technologies have higher treatment fee and unit construction costs. Ecological technologies have higher unit land use due to low treatment capacity. Both MBRs and constructed wetlands showed excellent performance in the 3E triangle.